Dermatomycoses In Diabetics - A Clinical Study - Parthiban K; Janaki C; Selvi Sentamil G; Janaki V R (Wolters Kluwer Medknow Publications, 1998)
Two hundred diabetics including 153 non- insulin dependent diabetes mellitus and 47 insulin dependent diabetes mellitus patients, were screened for mycoses. Candidiasis was the commonest mycoses, followed by dermatophtoses and pityriasis versicolor. The fasting blood glucose level was observed to be higher in candidialsis compared to other mycoses.